2012
DOI: 10.1186/1745-6215-13-78
|View full text |Cite
|
Sign up to set email alerts
|

An embedded longitudinal multi-faceted qualitative evaluation of a complex cluster randomized controlled trial aiming to reduce clinically important errors in medicines management in general practice

Abstract: BackgroundThere is a need to shed light on the pathways through which complex interventions mediate their effects in order to enable critical reflection on their transferability. We sought to explore and understand key stakeholder accounts of the acceptability, likely impact and strategies for optimizing and rolling-out a successful pharmacist-led information technology-enabled (PINCER) intervention, which substantially reduced the risk of clinically important errors in medicines management in primary care.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 47 publications
4
72
0
Order By: Relevance
“…A strength of this study was the use of quantitative and qualitative methods to give a broader understanding of how changeable this high-risk prescribing was, what the barriers to changing prescribing were and how GPs valued this work, which enabled informed choice of outcome measures and optimisation of the intervention 24 26 27. In addition, the findings supported the design of the trial process evaluation28 29 along with the main trial design.…”
Section: Discussionmentioning
confidence: 67%
“…A strength of this study was the use of quantitative and qualitative methods to give a broader understanding of how changeable this high-risk prescribing was, what the barriers to changing prescribing were and how GPs valued this work, which enabled informed choice of outcome measures and optimisation of the intervention 24 26 27. In addition, the findings supported the design of the trial process evaluation28 29 along with the main trial design.…”
Section: Discussionmentioning
confidence: 67%
“…Important differences were that PINCER targeted a broader range of prescribing topics than DQIP, that it was delivered over 12 weeks by pharmacists, and that it was more standardised in terms of how the pharmacists carried out medication reviews. However, the PINCER process evaluation did not explicitly examine the subcomponents of the intervention [28]. A systematic review of main trial evaluations of pharmaceutical and non-pharmaceutical interventions found evaluations of non-pharmaceutical interventions are significantly less likely to list ‘active ingredients’ (those elements of the intervention intended to lead to change in the outcome, [29], and we have not been able to identify any other process evaluations of cluster-randomised trials of multicomponent complex interventions which have examined the ingredients of complex interventions (although such studies are not easy to find because of poor labelling and reporting of process evaluations more generally) [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…37 Some 'errors' were over-ruled by GPs, however, on the basis of clinical experience of the patient, and there were also concerns about the long-term feasibility of pharmacists working in general practice. 38 Participants in the present study undertook informal case reviews of complicated multimorbid patients with their fellow GPs. Even without the rigorous processes of the MDT, participants benefited from the close proximity, ready availability, and generalist perspective of their colleagues.…”
mentioning
confidence: 99%